Some Accounting Consequences of Business Control by Overseas Chinese - Diga, Joselito; Craig, Russell (The International Journal of Accounting and Business Society, 1997)
This paper discusses some of the accounting consequences associated with the control of business enterprises by â€œoverseas Chinese" in the context of ï¬ve ASEAN countries. Based on extant research, overseas Chinese controlled business enterprises exhibit six characteristics with distinguish them Western multinational companies (MNCs): a family- centric corporate structure; exposure to diverse industries and commercial undertakings; a propensity to source ï¬nancing â€œin-houseâ€, increasing links with foreign MNCs though joint venture arrangements while attempting to maintain decision-making control locally; attitude towards intangible versus tangible assets; and decision-making which â€˜emphasises the use of balance sheets and cash ï¬‚ow statements. These characteristics raise questions regarding the applicability and appropriateness of Westem-based accounting standards and regulatory structures in regard to consolidation accounting based on legalistic notions of control, the practice of assigning values to intangible assets, and the decision-usefulness of ï¬nancial statements which use arbitrary cost allocations. The discussion here suggests that accounting practice in different national settings needs to be understood in terms ofunique set of cultural and organisational values.